Decrease in gamma-band activity tracks sequence learning - Madhavan, Radhika; Millman, Daniel; Tang, Hanlin; Crone, Nathan E.; Lenz, Fredrick A.; Tierney, Travis S.; Madsen, Joseph R.; Kreiman, Gabriel; Anderson, William S. (Frontiers in Systems Neuroscience, 2015)
Learning novel sequences constitutes an important example of declarative memory formation. Performance in sequence learning tasks improves with repetition and involves forming temporal associations over scales of seconds to minutes. To further understand the neural circuits underlying declarative sequence learning over trials, we tracked changes in intracranial field potentials from 1142 electrodes in fourteen human subjects while they learned the temporal-order of multiple sequences over trials through repeated recall. We observed a decrease in power in the gamma frequency band (30-100Hz) in the recall phase during the course of learning over trials, particularly in areas within the temporal lobe. Gamma power was directly correlated with the improvement in recall performance and was reset when learning new sequences. The decrease in gamma frequency band amplitudes over trials may reflect the need for plasticity early in the learning process combined with relatively reduced levels of plasticity required to maintain learned memory traces.